Strategi Promosi Destinasi Wisata Cibubur Garden Eat dan Play dalam Meningkatkan Kunjungan Wisatawan Melalui Instagram - Fitriya, Adinda; Kusumaningrum, Rastri; Mardiani Lubis, Flori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
West Java has now become a very popular tourist destination, showing a significant increase in the number of visits. Data from the West Java Provincial Tourism and Culture Office recorded more than 22 million domestic tourists and 1,156 foreign tourists until the third quarter of 2022. A special focus on Bogor, one of the main destinations in West Java, shows its popularity among domestic tourists, especially at Bogor Botanical Gardens and Taman Safari. The importance of destination marketing, especially through social media, is recognized as a key factor in long-term tourism development. Therefore, research was conducted by adopting Regina Luttrell's concept entitled